Morphology and anatomy of leaf, stem and petiole of Luvunga crassifolia Tanaka (Rutaceae) - Shunmugam, Sugathini; Rosli, Nur Syamilah; Manickam, Sugumaran; Mohd Yusoff, Nur Fatihah; Alitheen, Noorjahan Banu; Namasivayam, Parameswari (Penerbit UTM Press, 2021)
Luvunga crassifolia is an underutilized plant in the Citrus family. Other than brief morphological descriptions, there are no published reports on other identification features of this plant. Thus, the current study was aimed to investigate macroscopic and microscopic diagnostic features of L. crassifolia leaves, stems, and petioles. Macroscopic characterization, optimization of histological procedure, and histochemical analyses of differential stains were carried out on the leaves, stems, and petioles of L. crassifolia. The histological method was optimized by modifying the following parameters: number of fixation days, dehydration duration with degraded series of ethanol or butanol, clearing duration, and infiltration duration. After infiltration, embedding and sectioning of the tissues were performed. Histochemical analyses were carried out using differential stains to identify the cellular components in leaf, stem and, petiole tissue sections. This study showed that L. crassifolia leaves are amphistomatic. Pellucid dots were observed on both adaxial and abaxial leaf surfaces. Secretory cavities, xylem, phloem, and pericyclic fibers were found in the cross-sections of leaf, stem, and petiole. Calcium oxalates were present in the leaf and stem sections, while trichomes were detected in stem and petiole sections. The information obtained from this study will be helpful for the identification and future taxonomic-related studies of this plant species.